Computer Design of Robot ABB IRB 140 Transport System from Manufacturing Point of View - Novak-Marcincin, Jozef; Janak, Miroslav; Takac, Dominik (Manufacturing Technology Journal, 2014)
This paper presents the theoretical and practical aspects of industrial robots transport systems problems focused on application possibilities connected with concrete type of robotic device. Introduction of the article presents today possibility of robot transport systems and collect information about basic technical parameters of transport systems, their design and construction. Main part describe industrial robot ABB IRB 140, collect information about technical parameters, its construction, axes, motions and applications used in industrial practice. Practical part of paper is focused on proposal of robot transport system design from manufacturing point of view.
Keywords: industrial robot; transport system; manufacturing technology